2012
DOI: 10.1088/0031-9155/57/5/1191
|View full text |Cite
|
Sign up to set email alerts
|

Combined modulated electron and photon beams planned by a Monte-Carlo-based optimization procedure for accelerated partial breast irradiation

Abstract: The purpose of this study was to present a Monte-Carlo (MC)-based optimization procedure to improve conventional treatment plans for accelerated partial breast irradiation (APBI) using modulated electron beams alone or combined with modulated photon beams, to be delivered by a single collimation device, i.e. a photon multi-leaf collimator (xMLC) already installed in a standard hospital. Five left-sided breast cases were retrospectively planned using modulated photon and/or electron beams with an in-house treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 29 publications
(45 reference statements)
0
44
1
Order By: Relevance
“…By delivering MERT plans with a standard photon MLC, the potential arises for seamless mixed electron–photon delivery without interrupting treatment delivery between modality changes. Indeed, mixed‐beam electron–photon radiotherapy (MBRT) plans have been shown to offer additional degrees of freedom to influence the trade‐off between normal tissue dose and target coverage …”
Section: Introductionmentioning
confidence: 99%
“…By delivering MERT plans with a standard photon MLC, the potential arises for seamless mixed electron–photon delivery without interrupting treatment delivery between modality changes. Indeed, mixed‐beam electron–photon radiotherapy (MBRT) plans have been shown to offer additional degrees of freedom to influence the trade‐off between normal tissue dose and target coverage …”
Section: Introductionmentioning
confidence: 99%
“…If photon beams are added to electron beams, called mixed beam radiotherapy (MBRT), then this restriction in the target depth is removed. It was shown for targets with at least some superficial part that treatment plan quality of coplanar step and shoot MBRT plans with simultaneously optimized photon and electron beams is substantially improved compared to IMRT and VMAT plans, because of the additional DoF of two different particle types . At the same time, clinical workflow could be maintained, because photon and electron beams are usually both available on the same conventional treatment unit and using the pMLC also for electron beam collimation means that no accessory is required to be attached to the treatment unit.…”
Section: Introductionmentioning
confidence: 99%
“…In certain PBI cases, the dose distribution and OAR exposure may be optimized by the combination of photon and electron fields. [23][24][25] Only 1 contemporary study has reported the use of sole electron fields for PBI. 26,27 Altogether 40 patients with relatively small breasts received electron irradiation of a dose of 25 Â 2 Gy; this technique resulted in the lowest rate (17.5%) of fat necrosis of grade I to III, as compared with that in the brachytherapy and WBI arms.…”
Section: Clinical Outcomementioning
confidence: 99%